Eksistensi Mahasiswa Melalui Pengembangan Konten Edukasi Publik Berbasis Bahasa Digital Ditinjau dari Perspektif Filsafat Eksistensialisme - Nurhikmah Hidayah; Nadia Novita Sari; St. Zahra Al-Hidaya; Candra Dewi, Anita (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This research aims to analyze and describe the role of students in using TikTok as an educational platform. The method applied in data collection and analysis is a qualitative descriptive method. The subjects in this research were 3 TikTok creators, namely Rian Fahardhi, Husain Basyaiban, and Erika Richardo. The data used are videos uploaded by the three TikTok creators. Based on the research results, it can be seen that the existence of students in the digital era has an impact on learning among the general public. It is hoped that this research can provide deeper insight into the role of students in the digital era, so that it can improve the quality of learning and active participation among the general public.